OPTIMIZATION OF TRANSPARENT AND ACCOUNTABLE REGIONAL FINANCIAL MANAGEMENT AT THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY (BPKAD) OF EAST LAMPUNG REGENCY - Tathia Yolanda Arvaresa; M. Oktaviannur (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the optimization of transparent and accountable regional financial management at the Regional Financial and Asset Management Agency of East Lampung Regency. All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that: (1) Transparency Dimension: Regional financial management at the Regional Financial and Asset Management Agency of East Lampung Regency has been guided by the principle of openness; (2) Accountability Dimension: Regional financial management has been implemented in accordance with regulations; (3) Efficiency and Effectiveness Dimension: The use of the regional budget has not fully reflected optimal efficiency and effectiveness. (4) Management Systems and Information Technology Dimension: The use of financial management systems and information technology has assisted the regional financial administration process. (5) Supervision Dimension: Regional financial management has been implemented through internal and external mechanisms.